Martin Buber: a life of faith and dissent - Mendes Flor, Paul (Jewish Lives, 2019)
The first major biography in English in over thirty years of the seminal modern Jewish thinker Martin Buber. An authority on the twentieth-century philosopher Martin Buber (1878-1965), Paul Mendes-Flohr offers the first major biography in English in thirty years of this seminal modern Jewish thinker. Organized around several key moments-such as his sudden abandonment by his mother when he was a child of three-Mendes-Flohr shows how this foundational trauma left an enduring mark on Buber's inner life, attuning him to the fragility of human relations and the need to nurture them with what he would call a "dialogical attentiveness." Buber's philosophical and theological writings, most famously I and Thou, made significant contributions to religious and Jewish thought, philosophical anthropology, biblical studies, political theory, and Zionism. In this accessible new biography, Mendes-Flohr situates Buber's life and legacy in the intellectual and cultural life of German Jewry as well as in the broader European intellectual life of the first half of the twentieth century